2015
DOI: 10.1016/j.bpj.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Orientation and Order of the Amide Group of Sphingomyelin in Bilayers Determined by Solid-State NMR

Abstract: Sphingomyelin (SM) and cholesterol (Chol) are considered essential for the formation of lipid rafts; however, the types of molecular interactions involved in this process, such as intermolecular hydrogen bonding, are not well understood. Since, unlike other phospholipids, SM is characterized by the presence of an amide group, it is essential to determine the orientation of the amide and its order in the lipid bilayers to understand the nature of the hydrogen bonds in lipid rafts. For this study, 1'-(13)C-2-(15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…Texas-Red 1,2-palmitoyl-sn-glycero-3-phosphoethanolamine and 1-palmitoyl-2-oleoyl-phospatidyl choline (POPC) were purchased from Avanti Polar Lipid (Alabaster, AL). SSM was purified from bovine brain sphingomyelin (Avanti Polar Lipids) by reverse-phase high-performance liquid chromatography (14). Synthesis of ent-SSM (compounds 3 and 4 in Fig.…”
Section: Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…Texas-Red 1,2-palmitoyl-sn-glycero-3-phosphoethanolamine and 1-palmitoyl-2-oleoyl-phospatidyl choline (POPC) were purchased from Avanti Polar Lipid (Alabaster, AL). SSM was purified from bovine brain sphingomyelin (Avanti Polar Lipids) by reverse-phase high-performance liquid chromatography (14). Synthesis of ent-SSM (compounds 3 and 4 in Fig.…”
Section: Generalmentioning
confidence: 99%
“…The hydroxybearing chiral center is introduced by subsequent enzymatic reductions to produce D-erythro-sphingomyelin (2S, 3R) (13). These chiral centers likely contribute to the formation of intermolecular hydrogen-bonding, which has long been considered important for lipid-raft formation (14). A previous study using chemically modified sphingomyelins such as 3-O-methylated and 2-N-methylated analogs demonstrated that O-or N-methylation disrupts the intermolecular hydrogen-bonding network, which results in decreased gel formation and reduces the ordering effects of Cho (15).…”
Section: Introductionmentioning
confidence: 99%
“…Seventeen different site-selectively deuterated SMs were prepared and site-specific dynamics of SM was revealed in raft and non-raft membranes. In the third approach, the orientation of the SM amide plane in lipid bilayers was analyzed using dipolar couplings and CSAs [166] as described below.…”
Section: Dynamics Of Amphotericin B and Sphingomyelin In Membrane Bilmentioning
confidence: 99%
“…Total lipid concentration: 500 mM. (d) Conformation of the central region of SM in small isotropic bicelles (SSM/DHPC = 1:2) deduced from 1 H NMR spin–spin coupling constants (blue arrows) and NOEs (red arrows) …”
Section: Lipid‐raft‐related Molecules Conformation and Dynamicsmentioning
confidence: 99%
“…We also utilized small isotropic bicelles composed of SSM and DHPC ( q = 0.5) to determine the conformation of SM in isotropic bicelles on the basis of nuclear Overhauser effects and vicinal 1 H– 1 H coupling constants . The NOESY spectra provided conformationally relevant NOEs such as H‐3/H‐5, H‐2/H‐4, and NH/H‐3 (Figure d).…”
Section: Lipid‐raft‐related Molecules Conformation and Dynamicsmentioning
confidence: 99%